Biowaste compost effects on productive and qualitative characteristics of some field crops and on soil fertility - Giovanni Fecondo; Sabina Bucciarelli; Elvio Di Paolo; Giovanni Ghianni (Italian Journal of Agronomy)
Biowaste compost exploitation is a way of recovering agricultural soil fertility that in these last decades decreased up to a desertification limit. In order to test compost efficacy on crop yield and soil fertility, in the period 2011-2013 at COTIR experimental farm, a trial comparing different amounts of compost on two crop rotations was carried out. Crop rotations tested were durum wheat-sunflower-durum wheat and tomato-durum wheat-pepper. Results showed that the use of 40 t ha–1 of compost increased wheat grain yield and protein content if compared to control and mineral fertilised treatment. Compost application at 40 t ha–1 increased also yield of pepper in the first two harvest times, while during the third harvest, which included green and red berries, (the) yield was statistically different only if compared to control treatment. Moreover, compost improved soil fertility both in terms of organic matter and main nutritional elements, while a negative aspect of its use was the increase of soil electric conductivity, although no negative effect on crops yield were observed.